TheEffect of Color Plastic Mulches onGrowth, Yield and Quality of Two Hybrids of Summer Squash (cucurbita pepo l.) - Saeid, Abduljebbar I.; Mohammed, Ghurbat H. (Science Journal of University of Zakho, 2015)
This experiment was carried out at the vegetable research farm of Horticulture Department/ Faculty of Agriculture /Duhok University on two hybrids of summer squash during spring in the season of 2014, to study the effect of five color plastic mulches (without cover, transparent, black, red and blue) on two hybrids of summer squash (Amjed and Alexandra F1). The results showed that covers plastic mulches led to positive significant differences in leaf area (cm2), leaves chlorophyll content%, , fruit number/plant, early yield and total yield as well as fruit weight (g ), fruit length (cm) and fruit diameter (mm) as compared to without cover. There were no significant differences between the two hybrids in all detected traits. The interaction between covers plastic mulches and two hybrids was significantly enhanced all detected traits, since summer squash (Alexandra hybrid) covered with transparent plastic mulch were characterized by the highest values of leaf area (cm2), leaves chlorophyll content% and fruit diameter (mm), and summer squash (Amjed hybrid) covered with blue plastic mulch gave positive significant of fruit number/plant and total yields ton/ hectare